Examining customer relationship management from a management fashion perspective - Dag Øivind Madsen; Daniel Johanson (Cogent Business & Management, 2016)
Despite mixed performance reviews and experiences, customer relationship management (CRM) is among the most widely used and discussed management ideas by managers around the world. Commentators have noted that CRM has become “big business” and that there are many commercial actors selling CRM solutions. Despite such observations, little academic research has examined CRM using theories about management fads and fashions. Using management fashion theory as an analytical lens, this paper casts lights on the emergence and evolution of the market for CRM. The analysis of the supply side of CRM shows that many different actors have been involved, e.g. consulting firms, software vendors, industry analyst firms, and conference organizers. On the demand side, the interest in and usage of CRM remains relatively high despite mixed implementation experiences and failure cases. Based on the analysis, CRM has yet to enter into a downturn phase as is typical of transient management fashions. The longevity and staying power of the CRM fashion can partly be explained by institutional activities carried out by software firms, consultants, and IT industry analysts in training and certifying users, and in developing various complementary products and services. However, similar to what has been observed in relation to other management idea movements, a continuing high number of high-profile failure cases could “wear out” CRM. Therefore, the extent to which organizations are able to capitalize on CRM will likely shape the future trajectory of the CRM idea.
Keywords: 650